(untitled) (VERITAS LEGIS JOURNAL, 2025)
The article is devoted to a comprehensive analysis of the state of protection of the rights of women held in places of deprivation of liberty in the Republic of Kazakhstan. The key problems in the functioning of women’s correctional institutions are examined, including the non-compliance of detention conditions with international standards, insufficient provision of sanitary, domestic, and medical facilities, as well as the risks of gender-based violence and discrimination. Special attention is paid to the practice of applying criminal and penal enforcement legislation in relation to women, including the analysis of the institutions of parole, alternative sanctions, and amnesty. Based on official statistical data and specific cases, systemic problems in law enforcement practice are identified, demonstrating a formalistic approach by the courts and the prioritization of punitive mechanisms over the principles of humanism and the protection of human rights. The article substantiates the necessity of introducing a women’s amnesty as the first stage of reforming the penitentiary system and proposes directions for further transformations, including the demilitarization of the penal enforcement system, the introduction of gender-sensitive detention standards, and the expansion of public oversight. It is concluded that the implementation of Kazakhstan’s international human rights obligations requires consistent and systematic changes aimed at the humanization of punishment and the reintegration of convicted women into society.